A Audit Komprehensif Arsitektur Big Data, Hardening Keamanan Siber, dan Kepatuhan Regulasi pada Platform Telemedicine Menggunakan Standar OWASP - Hary Priyono; Yuliana Yawa (LPPM UNIVERSITAS INSAN PEMBANGUNAN INDONESIA, 2026)
The exponential growth of digital health services demands highly resilient, secure, and regulatory-compliant software architectures. This study executes a deep technical audit of the Alodokter telemedicine platform, addressing gaps in previous literature by integrating software engineering heuristics, Big Data architectural modeling, and rigorous cybersecurity vulnerability assessments based on the OWASP framework. Methodologically, the study employs quantitative heuristic evaluations, microservices reverse engineering, and conceptual penetration testing protocols. The empirical results demonstrate that while the UI/UX achieves an excellent mean satisfaction score (4.2/5), the virtual triage module lacks advanced Artificial Intelligence integration. Architecturally, the system leverages a robust hybrid data lake, isolating relational billing transactions (SQL DDL/DML) from unstructured clinical imagery via NoSQL clusters (Hadoop). From a cybersecurity perspective, the application mandates TLS 1.3 for in-transit data; however, the absence of mandatory Two-Factor Authentication (2FA) and exposure to API endpoints present severe Account Takeover risks. Furthermore, cryptographic hardening through AES-256 for Data-at-Rest is strongly recommended to comply with the Ministry of Health regulations and the Personal Data Protection Act (UU PDP). This paper concludes with strategic roadmaps for integrating HL7 FHIR standards to support national health interoperability.